Rare Case of Primary Effusion Lymphoma mimicking Pulmonary Tuberculosis - Idris, Dewinsya Medisujiannisa; Gubali, Winansih (Universitas Negeri Gorontalo, 2024)
Primary effusion lymphoma (PEL) is a rare large B-cell non-Hodgkin lymphoma (NHL) that usually occurs in immunosuppressed individuals in advanced stages of the disease, presenting as body cavity effusions without detectable tumor mass. We report a 61-years old man presented to the emergency room complaining of effort-related dyspnoea, low-grade fever, night sweats, and a dry cough for several days. He was then put on empirical anti-tubercular treatment (ATT) suspecting Pulmonary Tuberculosis. General examination revealed a decrease oxygen saturation, tachypnea, a bulging tenderness lymph node on the neck. Chest computerized tomography (CT) scan indicated pericardial and pleural effusion with mediastinal dilatation suspected thymoma or lymphoma. A Cardiocentesis needle aspiration was performed; however, the histological pattern was not specific. The patient underwent a surgical biopsy of a left supra-clavicular lymph node. A Classical Hodgkin lymphoma nodular sclerosis type was found in the histopathology examination. Immunohistochemistry detected the tumour cellular markers (i.e., CD30). Chemotherapy treatment for 6 cycles resulted an excellent outcome. In conclusion, radiologists play a vital role in the diagnosis of PEL, detecting effusions in body cavities and excluding the existence of solitary masses or pleural nodules or masses, ultimately narrowing down the differential diagnoses.